Do the swans deceive us all?. (8th November 2013) - Boyd, Brian
Abstract : A theoretically nuanced human–animal studies now stands at the forefront of many academic disciplines. The 'theoretical lag' characteristic of archaeology means that a subject largely reliant on the remains of humans and animals, and their associated material residues, lies lacking in theoretical sophistication.